IDENTIFICATION OF WHOLE GENOMES OF ENDOGENOUS RETROVIRUSES IN SIBERIAN MINIATURE PIGS - R. B. Aitnazarov (Vavilovskij Žurnal Genetiki i Selekcii, 2015)
Study of the populational dynamics of Siberian miniature pigs for the gag and env loci of endogenous pig retroviruses is reported. Currently, the frequency of carriers of types A, B, and C of PERV genomes in minipigs is high. Their breeding conducted from 2005 till 2013 increased the percentage of animals free from type B retroviruses.